Response to The COVID-19 crisis: a Comparative Analysis of The Actions of Indonesia, Mexico, and Croatia - Mikac, Robert; Kos-Stanisic, Lidija; Harahap, Ali Musa (LPPM Universitas Lampung, 2022)
The COVID-19 pandemic as a global crisis with significant consequences has caused numerous disruptions in the regular functioning of life, business processes, dynamics, and ways of working. The consequences created only in human losses are extremely high and the recession in which countries have entered, during which many companies have gone bankrupt. This crisis has shown that the world is not ready or able to solve global crises, and the response to the COVID-19 pandemic was primarily states' responses to crisis what should account for the urgency of the situation in short, medium and long-term phases. Therefore, it is necessary to research how states responded to the crisis and compare their activities and results. The reactions of countries within the same region can be assumed to be very similar because the crisis circumstances were almost the same. The research interest of this paper has been expressed according to the analysis of policy responses of Indonesia, Mexico, and Croatia. The research design is based on a quantitative-qualitative framework consisting of a desk-top analysis of available secondary data sources, crisis management theory, case study theory approach, and, cross-national analysis approach analyzing Indonesia, Mexico, Croatia the COVID-19 state pandemic preparedness and response policy.